Physical Sokoban An augmented reality game - Öjeling, Christoffer (My University, 2016)
An augmented reality version of the classical puzzle game Sokoban was developed. The user wears a virtual reality headset on their head. The game objects are virtually drawn on top of the video stream, and the game controlled entirely by moving a physical object. This thesis addresses the algorithmic and design requirements of such a game on low cost and performance constrained devices like smartphones. To this end a new algorithm for accurately tracking the position of the physical object in the video stream was developed. While the game is designed to be enjoyable by healthy users, it is made to in the future be used in rehabilitation — to aid patients with upper spinal cord injuries training grasping with their neuroprosthesis. To this end the game records various statistics about how the user plays — which in the future can be used to track and analyze patient progress. A user study carried out on healthy users indicates that the concept shows promise. Out of 10 participants, 9 answered yes to “I would like to play the game again”, rating their overall experience a mean of 7.2 out of 10 (higher is better).
Keywords: Data- och informationsvetenskap; Computer and Information Science